(untitled) (Medical Forum Monthly, 2020)
Objective: To compare mask and prong for delivery of CPAP in management of premature neonates with tachypnea in terms of frequency of CPAP failure. Study Design: Randomized controlled trial study. Place and Duration of Study: This study was conducted at the Department of Pediatrics, Holy Family Hospital Rawalpindi from September 2018 to February 2019. Materials and Methods: One hundred and twenty pre-term infants with gestational age from 27-34 weeks of any gender were included. They were divided in two groups; randomized to receive either mask (Group 1) and prong (Group 2) as a mode of NCAP delivery interface. Results: Comparison of mask versus prong for delivery of CPAP in management of premature neonates with tachypnea in terms of frequency of CPAP failure shows 5% (n=3) in Group 1 and 11.67% (n=7) in Group 2 with p value was 0.18. Conclusion: Mask for delivery of continuous airway pressure in management of premature neonates with tachypnea in terms of frequency of CPAP failurehas less frequency as compared to prong.